Modeling and analyzing the effects of seasonality on brucellosis infection. (November 2017) - Lolika, Paride O.; Mushayabasa, Steady; Bhunu, Claver P.; Modnak, Chairat; Wang, Jin
Abstract: We present a mathematical model for the transmission dynamics of brucellosis that incorporates the effects of seasonality. We analyze the basic reproduction number associated with the time-periodic model and establish results on the threshold dynamics. Meanwhile, we perform an optimal control study on the use of animal vaccination and environmental decontamination as disease control measures against brucellosis infection. Our results show that seasonality plays an important role in shaping the long-term dynamics of brucellosis, which subsequently impacts the design of its optimal control strategies.